History and perspectives of the Observatory on critical editions (Prassi Ecdotiche della Modernità Letteraria, 2021)
Speech presented at the seminar “Ecdotic practices. Philological seminars in memory of Giovanni Orlandi ", The Observatory on critical editions. A construction site in development, held in virtual form on 9 October 2020.